Epistolophilia : Writing the Life of Ona Simaite - Šukys, Julija (Book collections on Project MUSE., 2012)
The librarian walks the streets of her beloved Paris. An old lady with a limp and an accent, she is invisible to most. Certainly no one recognizes her as the warrior and revolutionary she was, when again and again she slipped into the Jewish ghetto of German-occupied Vilnius to carry food, clothes, medicine, money, and counterfeit documents to its prisoners. Often she left with letters to deliver, manuscripts to hide, and even sedated children swathed in sacks. In 1944 she was captured by the Gestapo, tortured for twelve days, and deported to Dachau. Through Epistolophilia, Julija Šukys fol.